Carry over effects of summ crops on virippu rice - Regina Lily Edwin (Department of Agronomy, College of Agriculture, 1989)
With a view to evaluate the carry over effects of different summer crops on virippu rice and to test the effects of three different levels of NPK, fertilizers on the growth and yield of rice, two filed experiments were conducted at the Instructional farm, college of Agriculture, Vellayani during 1987. The experiment was laid out in randomised block design with three replications. There were five summer treatments (grain type cowpea, daincha, sesamum, maize and fallow) preceding rice and three NPK levels tried on rice. The fertility levels were (i) F0 – No fertilizers. (ii) F1 – Half the recommended dose. (iii) F2 – Full recommended dose. The rice variety used was Jaya. The abstract of the results are given below. Daincha and cowpea resulted in the maximum number of tiller production. Proportionate increase in the number of tillers with the quantity of fertilizers was observed. Highest LAI of rice was observed after daincha. Daincha incorporation during summer recorded the maximum uptake of all the three nutrients by rice in the virippu season. Among the systems cowpea-rice depleted the soil of maximum quantity of nitrogen and potassium. P uptake was highest in the daincha-rice system. Application of full recommended dose caused maximum uptake of the major nutrients. The number of spikelets per panicle, number of filled grains per panicle, weight of the panicle and the test weight of rice crop were higher in the daincha- rice sequence. In general these yield attributes showed linear response to the quantity of NPK fertilizers in all the systems tried. The grain yield, straw yield, biomass production and harvest index of rice were maximum when it was preceded by a summer crop of daincha. With daincha incorporation insitu, half the recommended dose of NPK fertilizers (f1) was sufficient to get yields same as that of full compliment of NPK fertilizers (f2). In the other systems the results obtained were in proportionate to the quantity of fertilizers. The organic carbon, total nitrogen and available P2O5 content of the soil were highest after daincha and available potassium after cowpea. Among the sequences, daincha-rice system best maintained the total N and available P2O5 content available K2O of the soil. The three different fertility levels could exert no significant influence on the total nitrogen and the available P205 content of soil. A positive N balance was observed in the cowpea-rice and the daincha-rice sequences. In sesamum-rice, maize-rice and fallow-rice the balance was negative. The P balance of soil was maintained positive in all the sequences except fallow-rice. All the cropping sequences tried resulted in the positive balance of K. The three fertility levels could not exert any significant influence on the N and P balance of soil after the five sequences tried. The k balance of the soil was proportionate to the quantity of fertilizers in the daincha-rice, sesamum-rice and fallow-rice sequences. The sesamum-rice sequence was found to be the most profitable among the five sequences tried. Highest cost-benefit ratio was registered in the cowpea-rice system.